Rural incomes in the context of structural and agricultural transformation - Kennedy, Adam (International Food Policy Research Institute, 2018)
The agricultural sector of Asian middle-income countries is changing rapidly in line with an overall structural transformation of the economy brought about by economic growth. Dr. David Dawe of FAO discussed the changes taking place throughout Asia related to this agricultural transformation in his keynote address at the ReSAKSS-Asia event entitled “Agriculture and Rural Transformation in Asia: Past Experiences and Future Opportunities”. This brief summarizes some of the main points of his presentation while a more detailed discussion can be found in his earlier FAO working paper (Dawe, 2015).